Detection of High Cerebrospinal Fluid Levels of (1→3)-β-d-Glucan in Cryptococcal Meningitis. (26th November 2014) - Rhein, Joshua; Bahr, Nathan C.; Morawski, Bozena M.; Schutz, Charlotte; Zhang, Yonglong; Finkelman, Malcolm; Meya, David B.; Meintjes, Graeme; Boulware, David R.
Abstract : (1→3)-Beta-D-glucan was detected in high levels in cerebrospinal fluid, and to lesser extent in serum, among HIV-infected persons with cryptococcal meningitis. Abstract: Background.  (1→3)-β-d -Glucan (BDG) is a helpful diagnostic marker for many invasive fungal infections. However, BDG is not thought to be useful in diagnosing cryptococcosis. We evaluated the utility of BDG as an adjunct diagnostic tool for patients infected with human immunodeficiency virus (HIV) and presenting with suspected cryptococcal meningitis. Methods.  The Fungitell assay was used to measure BDG concentrations in cerebrospinal fluid (CSF) ( n = 177) and serum ( n = 109) of HIV-infected Ugandans and South Africans with suspected meningitis. Correlations between BDG concentrations and quantitative CSF cryptococcal cultures, CSF cryptococcal antigen (CRAG) titers, and 18 different CSF cytokine concentrations were assessed using non-parametric tests. Mixed models evaluated longitudinal changes in CSF BDG concentrations. Survival analyses were used to evaluate BDG's relationship with mortality. Results.  The Fungitell BDG assay provided 89% sensitivity and 85% specificity in CSF for cryptococcal meningitis. Serum sensitivity was suboptimal (79%). Cerebrospinal fluid BDG concentrations at diagnosis were median (interquartile range) 343 (200–597) pg/mL in cryptococcal patients and 37 (23–46) pg/mL in patients without cryptococcosis. Sensitivity in CSF improved to 98% (53 of 54) when initial fungal burdens were ≥10 000 colony-forming units/mL. (1→3)-β-d -Glucan normalized rapidly after initiating a.jpegungal therapy. Baseline BDG concentrations correlated with CSF fungal burden (rho = 0.820; P < .001), CSF CRAG lateral flow assay titers (rho = 0.780, P < .001), and monocyte chemotactic protein-1 levels in CSF ( P = .047). In patients with cryptococcal meningitis, BDG ≥500 pg/mL at diagnosis was associated with increased 10-week mortality. Conclusions.  (1→3)-β-d -Glucan is detectable in the CSF of HIV-infected patients with Cryptococcus, and it may provide useful prognostic information. Sensitivity is less than CRAG; however, BDG normalizes rapidly, unlike CRAG, making BDG potentially useful in diagnosing recurrent episodes.